Pengaruh Penerapan Media Kartu Huruf Hijaiyah Berwarna terhadap Kemampuan Membaca Huruf Al-Qur’an - Pudhak Prasetiyorini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of the application of colored hijaiyah letter media to the ability to read Al-Qur'an letters in children in group A Kindergarten Dharma Wanita Jember. This research is a type of quantitative research. The subjects of this study were group A students with a total of fifteen children. The results showed the average value of children before learning to use Hijaiyah color card media was 78.97 and the value after learning with the application of Hijaiyah color card media was 83.06. Paired sample t test results obtained ρ value 0,000. Teaching with these media can improve students' ability to read the Koran, complete learning objectives and make higher thinking activities for students. Conclusion, there is a statistically significant effect of the application of colored hijaiyah letter media to the ability to read the Koran in group A children of TK Dharma Wanita. Keywords: Hija'iyah Color Card, Reading Al-Qur'an, PAUD